To Publish or To Perish: The Common Plight of Authors, Graduate Students and Journal Editors - Tunku Ahmad, Tunku Badariah (IIUM Press, 2018)
In academia, so it seems, one of the only ways to make it to the top--or the only way to be promoted up the ladder of scholarship--is to publish frequently and in well-regarded journals. That seems to be the way to thrive and survive in the current academic world. As Murphy (2018) succinctly puts it, "publishing frequently and in top-tiered peer reviewed journals is the ticket to advancing in academia." For young researchers and new academics, this demand of the academic world may be a little overwhelming. Having to juggle between new teaching duties and supervisory roles and most likely family life, many might find it stressful and unattainable to publish frequently. For graduate students, the publication of at least one journal article based on their research has now been made a graduation requirement by numerous universities, so much so that many students have resorted to mindless copying and pasting from their theses in what they feel to be a publication feat. Thus, it is not surprising that many a time, the pressure to publish comes at the expense of originality and meaningful thought (Murphy, 2018), and this affects the quality of articles submitted for publication in journals.